Exploring the interaction between the capitate glandular trichomes of sunflower anthers and arthropods - Mazzei, Mariana Paola (2024)
Different floral traits mediate interactions between plants and their visitors. Capitates Glandular Trichomes (CGT) can attract or repel visitors, particularly arthropods. In Helianthus annuus L., CGTs are located at the distal ends of the anther appendages. This study aimed to determine whether the presence of CGTs influences the behaviour of diurnal floral visitors under field conditions by comparing genotypes with high and low CGT density per anther, while maintaining similar phenotypic characteristics. The analysis accounted for three random variables -floral developmental stages (R5.3, R5.6, and R6), daytime ranges (morning, midday, and afternoon), and two flowering seasons- to better understand variations in CGT mediated floral arthropod interactions. Key recorded species included Astylus atromaculatus (Blanchard) (Coleoptera Melyridae), Apis mellifera L. (Hymenoptera Apidae), and species from the Thomisidae family representing herbivores, pollinators, and insect-predators, respectively. The genotype with a high CGT density received fewer herbivore visits and more pollinator visits compared with the genotype with a low CGT density. Predators did not exhibit genotype-related differences but reduced bee presence by 20% probably due to Thomisidae spiders preying on bees. Furthermore, the inclusion of random variables enhanced the models. Herbivore abundance varied significantly between flowering seasons, while pollinator abundance fluctuated across the daytime ranges. Both herbivores and pollinators also showed variations in abundance across the reproductive stages, likely influenced by the proportion of disc floret phenophases and the CGTs´ secretory stage. This study underscores the importance of CGTs as a key morphological feature with potential implications for plant reproduction, justifying broader, more extensive investigations. It also emphasizes the necessity of considering multiple factors in plantarthropod interactions research.